Two Modified Spectrophotometric Methods for The Estimation of Indomethacin in The Pharmaceutical Formulations and Biological Fluids Using Bromate-Bromide Reagent, Indigo Carmine and Methyl Violet 2B Dyes - Saleem, Basima A.A.; Mohammed, Salim A.; Al-Taee, Amer Th. (Iraqi Journal of Science, 2026)
This research presents the development of two sensitive indirect spectrophotometric methods for the quantitative determination of indomethacin, applicable to its pure form, pharmaceutical formulations, and biological samples. The two methods A and B were developed based on the reaction of the drug indomethacin with bromine, which was generated in situ using an excess of the friendly environmental materials bromate-bromide mixture in an acidic medium through the principle of green chemistry. The residual amount of bromine reagent was then quantified by reacting it with either indigo carmine (method A) or methyl violet 2B (method B) dyes, and the absorbance of the remaining two dyes, with the absorbance of the remaining dyes measured at wavelengths of 610 nm and 582 nm, respectively. Both methods A and B follow Beer's law within the concentration ranges 1-22 and 0.4-18 µg/mL with an excellent molar absorptivity value 2.51×104 and 3.37×104 L/mol.cm, correspondingly. The accuracy values for both methods were calculated to be between 99.90% to 100.18%, and 99.97% to 100.12%, while a relative standard deviation (RSD%) in the ranges 0.1536 to 0.1959 and 0.0540 to 0.1293 for methods A and B, respectively. The evaluation of results of the two proposed methods was a achieved by applying t and F tests. The results showed that there is no significant difference between the proposed and reference methods. Both recommended methods A and B were used successfully to analyse indomethacin in its pharmaceutical forms (capsules, suppositories and spray), in the serum and urine, with no interference detected from excipients additives present in the commercial pharmaceutical preparations.